2015
DOI: 10.1186/s40497-015-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of perceived entrepreneurial ability in Catalonia: the individual and the entrepreneurial context

Abstract: Purpose: The main purpose of this study is to examine the antecedents of perceived entrepreneurial ability within a given context. Design/methodology/approach: Taking the cognitive approach we examine the role of several individual-level factors and the entrepreneurial context in the form of personal knowledge of other entrepreneurs and territorial location in influencing positive perceptions of entrepreneurial ability. The proposed hypotheses are tested on a dataset of 1961 respondents randomly selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Entrepreneurial ability is a combination of two important factors, viz., innate talent and continuous improvement of this talent (Sengupta et al, 2013). It is discussed in various literature that desire for profit (Bosma et al, 2012), social ties and networks (Hoang and Antoncic, 2003), prior experience, parental work background (Vaillant and Lafuente, 2007), awareness about one's entrepreneurial abilities (Bayon et al, 2015), market orientation are important factors that lead to enhance the entrepreneurial ability of an individual. Thus, a collective impact of entrepreneurial leadership and entrepreneurial ability can boost the individual entrepreneurial orientation and, subsequently the performance of the small business segment.…”
Section: Entrepreneurial Ability and Individual Entrepreneurial Orientationmentioning
confidence: 99%
“…Entrepreneurial ability is a combination of two important factors, viz., innate talent and continuous improvement of this talent (Sengupta et al, 2013). It is discussed in various literature that desire for profit (Bosma et al, 2012), social ties and networks (Hoang and Antoncic, 2003), prior experience, parental work background (Vaillant and Lafuente, 2007), awareness about one's entrepreneurial abilities (Bayon et al, 2015), market orientation are important factors that lead to enhance the entrepreneurial ability of an individual. Thus, a collective impact of entrepreneurial leadership and entrepreneurial ability can boost the individual entrepreneurial orientation and, subsequently the performance of the small business segment.…”
Section: Entrepreneurial Ability and Individual Entrepreneurial Orientationmentioning
confidence: 99%
“…In this way, it is critical to empower people with the entrepreneurial potential to have their spot in the economic procedures and process (Global Entrepreneurship Monitor Report, 2017/2018. Such studies focused on the contexts of organization, ethics, business, and community (Bayon et al, 2015). On the other hand, few pieces of research had been devoted to entrepreneurial activities and the reasons beyond having limitations in its applications.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Entrepreneurship and an individual's economic wellbeing are resulted from significantly connection with education abilities. As physical assets an individual's is a form of capital that provides long terms economic benefits; abilities can be acquired through education and training (Bayon et al, 2015). The abilities of human capital enhance the productivity of an individual.…”
Section: Entrepreneurial Action and Institutional Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to further research into the possible effects of culture at an individual level. Studies have suggested effects on entrepreneurship are due to individual differences: leadership traits (Stephan and Pathak, 2016), whether immediate family members (especially parents) have been entrepreneurial (Chrisman et al, 2002;Carr and Sequeira, 2007;Wongnaa and Kwame Seyram, 2014), whether childhood included any entrepreneurial experience (Drennan et al, 2005;Sharma and Madan, 2014), other individual educational experience (Peterman and Kennedy, 2003;Bayon et al, 2015), individual risk perception and information asymmetries (Palich and Bagby, 1995), and individual personality traits (Zhao et al, 2010) such as overconfidence (Bernardo and Welch, 2001). Recent research has begun to use complexity theory perspectives to argue that it is the various configurations of individual cultural components that drive entrepreneurial attitudes and intentions (Thai and Turkina, 2014;Woodside et al, 2016).…”
Section: Literature Of Culture and Entrepreneurshipmentioning
confidence: 99%